PEMBERIAN EKSTRAK AIR DAUN KATUK (Sauropus androgynus) DAN DAUN KELOR (Moringa oleifera Lam) MELALUI AIR MINUM TERHADAP DISTRIBUSI LEMAK DAN KOLESTEROL DARAH BROILER - I K., Widyanaya; Bidura, I G. N. G.; Candrawati, D. P. M. A. (Jurnal Peternakan Tropika; Vol 5 No 1 (2017), 2017)
The research aim to determine the provision of katuk leaves extract water (Sauropus androgynus) and moringa leaves (Moringa oleifera Lam) through the drinking water for fat distribution  and totally cholesterol of broiler blood. The research design with completely randomized design (CRD) with three treatments and six replications. Each replicates using three broiler aged two weeks with a homogeneous body weight. These three treatments are broiler given drinking water without the water extract of moringa leaves and katuk leaf as control (A), broiler given a water extract of katuk leaves 5% through drinking water (B) and broiler given a water extract of leaves of moringa 5% through the water drink (C). Rations and water were given ad libitum. The variables measured in the research are pads fat, mesentrium fat, ventriculus fat and blood totally cholesterol . The results showed that the percentage of pads fat of broiler drunk extracts of katuk leaves 5% water through drinking water (B) and broiler drunk water extract of moringa leaves 5% through drinking water (C), respectively 29,92% and 22,83% lower and significantly different (P<0.05) compared with treatment A. Mesentrium fat broilers treated B and broilers treated C, respectively were 8,00% and 12,00% lower but they were not significantly different (P>0.05) compared to the treatment A. Ventriculus fat of broiler are treated B and broilers treated C, respectively 23,08% and 17,31% lower significantly (P<0,05) compared with treatment A. While for blood totally cholesterol of broiler given treated B and treated C, respectively 9,34% and 8,62% were significant different (P<0.05) lower compared with treatment A. Based on the results of this research concluded that the giving of katuk leaves (Sauropus androgynus) and of Moringa leaves (Moringa oleifera Lam) water extract by 5% through drinking water can lower the percentage of pads fat, ventriculus fat and blood totally cholesterol of broiler.
Keywords: Sauropus androgynus, Moringa oleifera Lam, fat, cholesterol, broiler